ASEAN Awareness of Filipino High School Students: Basis for Promotional Strategies - Andres, Brenson Y. (Alipato, A Journal of Basic Education; Vol 9 (2018), 2018)
The Association of Southeast Asian Nations (ASEAN) is often described as the most exemplary regional project in the developing world. Though it has been relatively successful for the past five decades, one perennial critique of the organization is its failure to engage the greater number of people in its endeavors. This results to citizens’ low awareness and shallow understanding of the nature of the regional organization.  In light of the ambitious ASEAN Community launched in 2015, it is important to gauge the ASEAN awareness of Filipinos, particularly the youth sector which is viewed as the region’s future drivers and leaders. Utilizing a descriptive survey research involving Grades 7 to 10 students of a laboratory school in Quezon City, the study aims to: (1) to assess the respondents’ basic knowledge of ASEAN in terms of member-states, founding date, and flag; (2) to identify their primary sources of information about ASEAN; and (3) to devise promotional strategies to increase Filipinos’ ASEAN awareness based on their suggestions. Some of the secondary information and survey questions are adapted from Thompson and Thianthai’s (2007) Awareness of and Attitudes towards ASEAN: Findings from a Ten Nation Survey of University Students. General findings on the respondents’ ASEAN knowledge mirror the conclusion of Thompson and Thianthai’s (2007) study – “Filipino students are among the least cognizant of ASEAN as a regional grouping.” Furthermore, the results exhibited a significant divide between the ASEAN knowledge and sources of information of Grades 7-8 and 9-10 students. Such phenomenon proves that the Social Studies curriculum, particularly lessons on Regionalism in Asian History and Civilizations, plays a crucial role in the development of respondents’ ASEAN awareness. To further improve Filipino youth’s ASEAN awareness, four key suggestions regarding its more effective promotion were noted in the study.   Keywords: ASEAN, ASEAN awareness, education